Development of an Educational Model for the Prevention of Chronic Kidney Failure in Adolescents in the Form of Comics at Muhammadiyah Middle School, East Jakarta - Dewi, Nurma; Suryati, Sri; Narji, Moh (LPPM Universitas Mohammad Husni Thamrin, 2025)
Chronic kidney disease (CKD) is a global health problem with increasing prevalence, including among adolescents. Basic Health Research (Riskesdas) data shows an increase in the prevalence of chronic kidney disease from 7.0% in 2013 to 19.33% in 2018. This condition is influenced by risk factors such as hypertension, diabetes mellitus, and an unhealthy lifestyle, which in young people is often associated with lack of physical activity, poor diet, insufficient sleep, and smoking. If left untreated, hypertension can progress to CKD, which requires hemodialysis, impacting adolescents' productivity and future. Preventive efforts require effective, engaging, and easy-to-understand health education strategies. This study aims to develop and test the effectiveness of comic media in increasing adolescents' knowledge about CKD prevention. The study used a mixed methods design with a research and development approach, involving 30 randomly selected students from Muhammadiyah Middle School in East Jakarta. The research instruments included a media feasibility test by material experts and media experts, as well as a pre-test and post-test of respondents' knowledge. The results showed that comic media was considered very effective by both material experts (97.5%) and media experts (≥82%). Students' knowledge significantly increased from 64.44 to 75.97 (p=0.001) with an N-Gain value of 0.33 (moderate category). In conclusion, comic media is effective as a health education tool to increase adolescents' knowledge in preventing CKD.